Scientific journals play an important role in disseminating results of investigations, as well as criticism of the established knowledge (1). Their quality depends among other aspects, the speed of the selection process and publication (editorial process) - Robles Alfaro, Ricardo (2015)
Scientific journals play an important role in disseminating results of investigations, as well as criticism of the established knowledge (1). Their quality depends among other aspects, the speed of the selection process and publication (editorial process) Articles (2).